(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The purpose of this paper is to analyze the consequences arising on abortion rights in the wake of the U.S. Supreme Court decision (Dobbs et al, v. Jackson Women’s Health Organization, et al. 597 US_2022), delivered on June 24, 2022, that overturned the precedents of Roe v. Wade (1973) and Planned Parenthood v. Casey (1992), thereby eliminating, in this way, any existing federal protections.